Semi-actively Implemented Non-linear Damping for Building Isolation Under Seismic Loadings - Zhu, Yun-Peng; Lang, Zi-Qiang; Kawanishi, Yosuke; Kohiyama, Masayuki (Frontiers in Built Environment, 2020)
It is well known that semi-active solution can achieve building isolation with much less energy requirements than active solutions. Also, it has been shown in previous studies that compared to linear damping, nonlinear damping performs better for building isolation under sinusoidal ground motions. The present study is concerned with the extension of the application of the semi-actively implemented nonlinear damping to building isolation under seismic loadings. A two-degree-of-freedom (2-DOF) scaled building model is used for simulation studies. Experimental tests on a physical building model have been used to validate the effectiveness of the 2-DOF scaled building model in representing the behaviours of a physical building structure. The optimal design of the semi-actively implemented nonlinear damping for building isolation under design seismic motions is then carried out using the 2-DOF scaled building model based on simulation studies. The results show that an optimal design of semi-actively implemented nonlinear damping can improve the performance of building isolation under design seismic motions in terms of both absolute acceleration and inter-storey drift.